2017
DOI: 10.1038/s41550-017-0060
|View full text |Cite|
|
Sign up to set email alerts
|

The large-scale nebular pattern of a superwind binary in an eccentric orbit

Abstract: Preplanetary nebulae (pPNe) and planetary nebulae (PNe) are evolved, mass-losing stellar objects that show a wide variety of morphologies. Many of these nebulae consist of outer structures that are nearly spherical (spiral/shell/arc/halo) and inner structures that are highly asymmetric (bipolar/multipolar) [1,2]. The coexistence of such geometrically distinct structures is enigmatic because it hints at the simultaneous presence of both wide and close binary interactions, a phenomenon that has been attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 30 publications
3
58
2
Order By: Relevance
“…Assuming a circular orbit, the orbital period can be estimated from the slope of the observed emission in the angle-radius plot 40 , which for OH 26.5+0.6 yields ∼430 years. Another method exploits the spiralarm spacing 39,41 .…”
Section: Methodsmentioning
confidence: 99%
“…Assuming a circular orbit, the orbital period can be estimated from the slope of the observed emission in the angle-radius plot 40 , which for OH 26.5+0.6 yields ∼430 years. Another method exploits the spiralarm spacing 39,41 .…”
Section: Methodsmentioning
confidence: 99%
“…However, our results would tend to indicate a longer orbital period (by a factor of two or so) than that tentatively reported by D15. The TOPP observations cannot directly constrain the orbital eccentricity, that could very well be significant as a consequence of the mass loss and mass exchange between the binary components (e.g., Bonačić Marinović et al 2008;Kim et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, spirals can often be seen instead as concentric arcs. Ways to derive properties of the binary system based on the CSE morphology are discussed in Huggins et al (2009), Kim and Taam (2012c), and Kim et al (2013), and interpretations of observed morphologies through hydrodynamical simulations can be found in, e.g., Maercker et al (2012) and Kim et al (2017), Fig. 21, right panel.…”
Section: Impacts Of Companions On Cse Morphologymentioning
confidence: 99%
“…The number of examples is steadily increasing, e.g., CW Leo Decin et al 2015), RW LMi (Dinh-V-Trung 2009;Claussen et al 2011;Kim et al 2015), R Scl , R Aqr and W Aql (Mayer et al 2013), and π 1 Gru . A prominent example is that of the dust and gas spiral towards AFGL3068 (Mauron and Huggins 2006;Kim et al 2017), Fig. 21, left panel.…”
Section: Impacts Of Companions On Cse Morphologymentioning
confidence: 99%